Late Lutetian (Eocene) mafic intrusion into shallow marine platform deposits north of the Oman Mountains (Rusayl Embayment) and its tectonic significance. (October 2020) - Scharf, Andreas; Sudo, Masafumi; Pracejus, Bernhard; Mattern, Frank; Callegari, Ivan; Bauer, Wilfried; Scharf, Katharina
Abstract: A silica undersaturated alkali-olivine basanitic magma intruded the late Paleocene/early Eocene Jafnayn Formation near Muscat. Geochemical analyses indicate that a significant amount of host rock (limestone) was assimilated into the magma. We dated the basanite as 42.7 ± 1.0 Ma (2 sigma error; late Lutetian), using the whole rock 40 Ar/ 39 Ar step-wise heating technique. Intrusion occurred in the hanging wall of a major regional extensional shear zone (Frontal Range Fault, FRF) bounding the northern margin of two domes within the Oman Mountains (Jabal Akhdar and Saih Hatat domes). Two shear intervals along the FRF have been documented. The first interval lasted immediately after emplacement of the Semail Ophiolite (latest Cretaceous-early Eocene) while the second and poorly constrained interval was assumed to have occurred during the Oligocene. The proximity of the basanite to the FRF suggests that magma used extensional faults for the upper part of its ascent path. Reactivated Permian rift faults of the Pangaea rift or other preexisting faults may have been used for the lower ascent part. We conclude that the basanite intrusion coincided with the onset of the second deformation interval along the FRF, because (1) the position of the basanite is near a dextral releasing bend, associated with the second shear interval, (2) the overlap of our 40 Ar/ 39 Ar age with the cooling curves for rocks from the nearby Jabal Akhdar Dome, and (3) the basanite postdates the first FRF deformation episode by > 10 Ma. Thus, the second interval along the FRF had started already during the late Lutetian and probably lasted into the Miocene. Highlights: Basanite intrusion in the faulted margin of a major dome has a late Lutetian age. Ascent path of magma was along preexisting crustal-scale fault system. Extensional shearing probably lasted from the late Lutetian to the Miocene. Intrusion correlates with major extensional shearing during gravitational collapse. Carbonatic host rock were assimilated during intrusion.